Relationships between hamstrings-to-quadriceps ratio and variables describing countermovement and drop jumps - Struzik, A.; Pietraszewski, B. (Applied Bionics and Biomechanics, 2019)
The impact of the hamstrings-to-quadriceps ratio on sport movement performance has not been sufficiently described. However, it seems that in movements involving eccentric-concentric muscular contractions, a higher hamstrings-to-quadriceps ratio should have a positive impact on human movement performance. The present study is aimed at identifying relationships between the hamstrings-to-quadriceps ratio and variables describing countermovement and drop jumps. The study was carried out in a group of 14 female soccer players. The tests were conducted using a Kistler force plate, an SG electrogoniometer, and the Biodex System 4 Pro dynamometer. Each player performed three countermovement jumps (CMJ) and three drop jumps (DJ) from heights of 15, 30, 45, and 60?cm. The peak torques of knee extensors and flexors were measured in isometric conditions and in isokinetic conditions at angular velocities of 30o/s, 60o/s, 90o/s, and 120o/s. Statistically significant relationships were found between the variables that describe CMJ, DJ 15, DJ 30, and hamstrings-to-quadriceps ratio at some, though not all, of the angular velocities measured. No significant relationships were found between the hamstrings-to-quadriceps ratio and variables that describe DJ 45 and DJ 60. The heights of CMJ, DJ 15, and DJ 30 were increased with higher hamstrings-to-quadriceps ratios. Analogous relationships were found between the hamstrings-to-quadriceps ratio and relative mechanical power during the take-off phase of the CMJ. Significant relationships between the hamstrings-to-quadriceps ratio and variables that describe vertical jump are likely to be observed if adequate angular velocity is used in the measurement of muscle torque.